Analisis pembingkaian tajuk berita jenayah dalam Bahasa Melayu dan terjemahannya kedalam Bahasa Tamil / Parimala Gunasekaran - Parimala , Gunasekaran (2018)
Crimes occur every day because human instincts cannot be controlled from committing crimes. (Sinar Harian Press, September 2, 2013). The mass media plays a very crucial role in shaping the public attitudes by reporting crimes. One of the influential mass media conduits is the press. Like in many other countries, the press is the major print media in Malaysia (Jamudin Idris, 1996). Thus, the press has the important responsibility of delivering the right information as the power to shape the mental acuity of its readers lies in its hands. The overall aim of this study is to conduct an analysis on the framing of crime news headlines in Malay (source text) in comparison to their translations into Tamil (target text). Its specific objectives are as follows: (1) To identify how the Malay crime news headlines are framed in contrast to their translations in Tamil and, (2) to investigate the extent to which the crime news headlines in Malay compared to their translations in Tamil fulfill the criteria of clarity, accuracy, brevity and attractiveness. This study employs the theory of framing as proposed by Iyengar (1991 & 2009) and Semetko and Valkenburg (2000) as its theoretical framework to fulfill objective 1 while Crystal’s (1969) and Lamb’s (1985) is employed for objektif 2. Crystal (1969), states that a news headline should be “clear”, “succinct”, and should “have an intriguing message, to kindle a spark of interest” while Lamb emphasizes on the need for accuracy. The data for this study was collected from a number of Malay newspapers for a period of a month that is from 1 May 2014 to 30 May 2014. The translations in Tamil were done by four experienced translators working at Nam Naadu Media in Kuala Lumpur. The findings of this study revealed that the episodic, conflict and consequences frame are the main frames used in the coverage of crime news headlines in both the Malay and Tamil press media. The researcher also found that the Tamil crime news headlines placed more importance on achieving clarity and completeness of the message or accuracy compared to the Malay crime news headlines. As a result of this, the Tamil crime news headlines used more lexical items than the Malay ones. In the Malay data, there are a number of examples of crime news headlines that are incomplete and therefore vague or unclear. Finally, the analysis also revealed that the Malay crime news headlines which tend to be more succinct than the Tamil ones are also relatively more figurative in nature as they use metaphors. The findings of this study can benefit journalists and translators working in media agencies in Malaysia on the concept of framing. The study also recommends a number of approaches and strategies that should be considered by the media to construct crime news headlines which are more accurate, clear, succinct and attractive both in Malay and Tamil.